3D Graphene Network Encapsulating Mesoporous ZnS Nanospheres as High‐Performance Anode Material in Sodium‐Ion Batteries. Issue 12 (30th May 2018) - Hu, Liang; Hu, Xiang; Lin, Zhoubin; Wen, Zhenhai
Abstract: The front cover artwork is provided by the group of Zhenhai Wen from the Fujian Institute of Research on the Structure of Matter, Chinese Academy of Sciences (China). The image shows the hybrid structure of rGO enwrapping ZnS nanospheres can effectively restrict volume expansion and promote the cycling stability of sodium‐ion batteries. Read the full text of the Article at 10.1002/celc.201800412 . Abstract : " Zinc sulfide nanospheres enwrapped in a three‐dimensional network of reduced graphene oxide (rGO) are synthesized. Characterization of the composite material reveals a synergistic effect of the mesoporous nanostructure of the ZnS spheres and rGO enwrapping, leading to favorable features for the application as anode material in sodium‐ion batteries. These features include a good cycling stability and a good rate capability …" Find out more about the story behind the front cover research at 10.1002/celc.201800412 .